Human Behavioral Ecology and Historical Contingency: A Comment on the Diablo Canyon Archaeological Record. Issue 3 (20th July 2010) - Hildebrandt, William R.; McGuire, Kelly R.; Rosenthal, Jeffrey S.
Abstract : Using data from a single site along the central California coast (CA-SLO-2), Jones et al. (2008) critique our use of human behavioral ecology to explain changing hunting and fishing adaptations in prehistoric California and the Great Basin. Instead, they argue that human adaptations tend to stay relatively stable over time until they are influenced by historical contingencies. We question the utility of using data from a single site, and expand the sample with information from several deposits along the south-central coast. This expanded sample documents a dynamic evolutionary sequence characterized by increasing residential stability accompanied by hunting and fishing in more distant resource patches. Access to these patches, both terrestrial and marine, was made possible by changes in social organization and technology. Many of these behaviors appear to have incurred high costs, and are potentially explained with reference to costly signaling theory.